Mathematical Thermodynamics of Complex Fluids: Cetraro, Italy 2015 - Ball, John M (Lecture Notes in Mathematics, 2017)
The main goal of this book is to provide an overview of the state of the art in the mathematical modeling of complex fluids, with particular emphasis on its thermodynamical aspects. The central topics of the text, the modeling, analysis and numerical simulation of complex fluids, are of great interest and importance both for the understanding of various aspects of fluid dynamics and for its applications to special real-world problems.  New emerging trends in the subject are highlighted with the intent to inspire and motivate young researchers and PhD students.